Proximal vs. Total Gastrectomy: Is There a Difference in Quality of Life for Patients?. Issue 3 (March 2023) - Irfan, Ahmer; Yang, Tianjiao; Bowring, Mary; Blair, Alex B.; Duncan, Mark
Background: Proximal gastrectomy (PG) has been excluded from the arsenal of western surgical oncologists for fear of bile reflux and diet intolerance. However, it is often an appropriate, less morbid operation for patients requiring resection of a proximal gastric cancer. Methods: Between 2013 and 2017, we performed 19 PG and 37 total gastrectomies (TGs), of whom 15 and 25 were alive at the time of data collection. In this single-center series, we present findings of a 10-question interview of patients who underwent proximal (n = 8) or TG (n = 16) regarding postgastrectomy food-related symptoms, based on a modified version of the validated Postgastrectomy Syndrome Assessment Scale. Results: Out of 7 Likert scale questions, there were no statistically significant differences between the groups regarding bile reflux, early satiety, appetite, energy level, physical activity limitations, pain, or general dissatisfaction with their surgery. Patients from both groups reported eating similar amounts of their preoperative volume per meal and overall food volume for the day. Both groups reported eating a similar number of snacks and meals throughout the day. Food satisfaction scores, calculated by summation of the Likert scores, were not different. Conclusion: Although limited by the small population, we did not find a clinically relevant difference in food-related symptoms comparing PG and TG patients. This pilot study suggests that PG is an appropriate alternative to TG in certain populations. Anecdotal beliefs regarding potential bile reflux or diet intolerance should be reconsidered.